Efficacy of Chinese traditional patent medicines for heart failure with preserved ejection fraction: a Bayesian network meta-analysis of 64 randomized controlled trials - Guo, Hongxin; Zhu, Mingjun; Yu, Rui; Li, Xingyuan; Zhao, Qifei (Frontiers in Cardiovascular Medicine, 2023)
Background Heart failure with preserved ejection fraction (HFpEF) is associated with substantial morbidity and mortality, and modern medicine offers less effective treatment for HFpEF. Much evidence shows that Chinese traditional patent medicines (CTPMs) have good efficacy for HFpEF, but the advantages and disadvantages of different CTPMs for HFpEF are still unclear. This study used network meta-analysis (NMA) to compare clinical efficacies of different CTPMs for HFpEF. Methods Randomized controlled trials (RCTs) of CTPMs for treating HFpEF were searched in seven Chinese and English databases from inception to September 2023: China National Knowledge Infrastructure (CNKI), Wanfang, VIP, China Biology Medicine, PubMed, Cochrane Library, and Embase. Two researchers independently screened the literature, extracted data, and evaluated the quality of the included studies. The GeMTC package in R (version 4.1.2) was used to perform Bayesian NMA. Results A total of 64 RCTs were included, involving six CTPMs and 6,238 patients. The six CTPMs were Qili Qiangxin capsule (QLQXC), Qishen Yiqi dropping pill (QSYQDP), Yixinshu capsule (YXSC), Yangxinshi tablet (YXST), Shexiang Baoxin Pill (SXBXP), and Tongxinluo capsule (TXLC). Conventional Western medicine (CWM) treatment was given to the control group, and CWM treatment combined with CTPM treatment was given to the experimental group. The results indicated that CPTMs + CWM were all superior to CWM alone; SXBXP + CWM had the best efficacies in improving the New York Heart Association cardiac functional classification efficiency; TXLC + CWM was best at improving the ratio of early diastolic mitral inflow velocity to late diastolic mitral inflow velocity (E/A); QSYQDP + CWM was best at reducing N-terminal pro-B type natriuretic peptide (NT-proBNP); and QSYQDP + CWM was best at improving the 6-min walking test. In terms of safety, there was no signiﬁcant difference between CTPMs + CWM and CWM. Conclusion Compared with CWM alone, CTPMs + CWM combinations have certain advantages and good safety in the treatment of HFpEF. QSYQDP + CWM and SXBXP + CWM may be the potential optimal integrative medicine-based treatments for HFpEF. Given the limitations of this study, further high-quality, multicenter, large sample, randomized, and double-blind studies are needed to confirm the current results. Systematic Review Registration identifier, CRD42022303938.